2020
DOI: 10.1088/1361-6587/ab5b1d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the pedestal transport during edge localized mode cycles at ASDEX Upgrade

Abstract: The dynamic behaviour of the ion and electron energy, particle and momentum transport measured during type-I edge localized mode (ELM) cycles at ASDEX Upgrade is presented. Fast measurements of the ion and electron temperature profiles revelead that the ion and electron energy transport recover on different timescales, with the electrons recovering on a slower timescale (Cavedon et al 2017 Plasma Phys. Control. Fusion 59 105007). The dominant mechanism for the additional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 71 publications
(98 reference statements)
2
19
0
Order By: Relevance
“…This is consistent with our discussion in § 6.2 and the observation that the energy transport in pedestals reaches significant neoclassical levels only in the middle of a pedestal and not at the top and bottom (Viezzer et al. 2020). If instead we had chosen profiles with a stronger temperature gradient such that , we could have been able to retrieve a growing energy flux throughout the pedestal.…”
Section: Transport Equations and Flux Conditionssupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with our discussion in § 6.2 and the observation that the energy transport in pedestals reaches significant neoclassical levels only in the middle of a pedestal and not at the top and bottom (Viezzer et al. 2020). If instead we had chosen profiles with a stronger temperature gradient such that , we could have been able to retrieve a growing energy flux throughout the pedestal.…”
Section: Transport Equations and Flux Conditionssupporting
confidence: 93%
“…In pedestals, for example, strong gradients of temperature, density and radial electric field of the order of the inverse ion poloidal gyroradius are observed (Viezzer et al 2013). Moreover, it has been found that the ion energy transport in pedestals is close to the neoclassical level (Viezzer et al 2018). Measurements of H-mode pedestals in Alcator C-Mod (Theiler et al 2014;Churchill et al 2015) and Asdex-Upgrade (Cruz-Zabala et al 2022) have shown poloidal variations of density, electric field and ion temperature that cannot be explained using standard neoclassical theory.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The largely broadened ion pedestal can lead to a stronger response of T i,ped despite the decrease of ion pedestal gradient. In addition, ion pedestal is known to be heavily influenced by neoclassical transport 15,37,38 . Here, neoclassical heat flux by RMPs is roughly proportional to I 2 RMP , and it increases more rapidly with the smaller radial electric field and its gradient 39,40 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the pedestal heat diffusivity does not change much during 7.1-7.7 s, indicating that it is insensitive to the decreasing I RMP . It has been reported that the neoclassical transport effect dominates ion heat transport under RMPs 37,38 . However, this collisional transport strongly depends on the RMP strength.…”
Section: Resultsmentioning
confidence: 99%